Sarcopenia is attenuated by TRB3 knockout in aging mice via the alleviation of atrophy and fibrosis of skeletal muscles. Issue 4 (25th February 2020) - Shang, Guo‐Kai; Han, Lu; Wang, Zhi‐Hao; Liu, Ya‐Peng; Yan, Sen‐Bo; Sai, Wen‐Wen; Wang, Di; Li, Yi‐Hui; Zhang, Wei; Zhong, Ming
Abstract: Background: Sarcopenia causes several adverse events in elderly people. Muscle fibre atrophy and interstitial fibrosis are the main histopathological changes in sarcopenia and account for decreased muscle function. Tribbles homologue 3 (TRB3) was previously reported to exhibit age‐related expression and play a vital role in cell proliferation, differentiation, and fibrosis. We aimed to investigate how TRB3 affects sarcopenia. Methods: Wild‐type and TRB3 knockout C57/BL6J mice were randomly divided into young and old groups. Exercise capacity was evaluated, and single‐muscle function was detected by electrophysiological techniques, after which the mice were sacrificed to collect their gastrocnemius muscles for assessment of atrophy and fibrosis by histopathological and molecular biological methods. TRB3 expression, autophagy level, and MAPK signalling pathway activity were evaluated through western blotting. The interaction of TRB3 with P62 and the association between TRB3 and the MAPK signalling pathway were detected by co‐immunoprecipitation. Results: In aged mice, exercise capacity and cross‐sectional area of skeletal muscle fibres were decreased significantly, whereas TRB3, atrophy‐related markers atrogin 1 and MuRF 1, and interstitial fibrosis, including collagen volume fraction, contents of collagens I and III, and ratio of collagens I to III, were increased significantly ( P < 0.05 for all). Following TRB3 knockout, the cross‐sectional area of muscle fibres, mainly fast fibres, was elevated ( P < 0.05 for both), the atrogin 1 expression was decreased ( P = 0.0163), and the corresponding tetanic force of fast muscles was increased ( P = 0.0398). Conversely, interstitial fibrosis was substantially decreased and exercise capacity was significantly increased in the knockout mice. In terms of the underlying mechanisms, the autophagy receptor p62 was markedly increased and the MAPK signalling pathway was activated in aged skeletal muscles, which might be attributed to the interaction of TRB3 with p62 and MAPKKs, including MEK1/MEK2, MEK3/MEK6, and MEK4/MKK4. Notably, TRB3 knockout reduced the accumulation of p62 and LC3 ( P < 0.05 for both), decreased the phosphorylation of JNK ( P = 0.0015), and increased p38 phosphorylation ( P = 0.0021). Conclusions: TRB3 knockout in mice attenuated muscle fibre atrophy and reduced skeletal muscle fibrosis by increasing autophagy and inhibiting the MAPK signalling pathway. Correspondingly, in aged knockout mice, exercise capacity was improved. Interfering with TRB3 expression in aged skeletal muscles may serve as a target for the prevention and treatment of age‐related sarcopenia.